Mengidentifikasi Faktor-Faktor yang Mempengaruhi Tingkat Kepuasan Wisatawan di Green Gumuk Banyuwangi melalui Pendekatan Customer Index-Satisfaction (CSI) dan Regresi Logistik Ordinal - Nimas Ayu Prabawani; Khoirunisa Khoirunisa; Steven Ronis Pangaribuan (Lembaga Pengembangan Kinerja Dosen, 2025)
The tourism sector is a priority area for both national and regional economic development, as it contributes to increasing regional income. According to the Ministry of Tourism and Creative Economy (2023), Indonesia’s tourism sector contributes more than 4% to the Gross Domestic Product (GDP) and is a development priority based on local advantages. Green Gumuk Candi Banyuwangi is a nature- and education-based tourist destination that has experienced rapid development in recent years. However, it has not been extensively evaluated scientifically in terms of visitor satisfaction. This study aims to measure the level of visitor satisfaction at Green Gumuk Banyuwangi using the Customer Satisfaction Index (CSI) method and to analyze service-related factors that significantly influence satisfaction using ordinal logistic regression. The CSI scores for facility conditions, service quality, and overall visitor satisfaction were 0.82, 0.86, and 0.84, respectively, indicating a very high level of satisfaction. The ordinal logistic regression analysis concluded that service quality significantly influences the level of visitor satisfaction at Green Gumuk Banyuwangi, with a prediction accuracy rate of 94%.